Implementation of Differentiated Learning to Improve Student Learning Effectiveness in Islamic Education Learning at Widya Dharma Private Elementary School, PT. Asam Jawa - Sumarni; Fitriyana; Siagian, Zulena (Journal of Indonesian Primary School, 2024)
This study aims to Improve the Effectiveness of Student Learning in Islamic religious education learning by using Differentiated Learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. Tests are used to measure the Effectiveness of Student Learning and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Differentiated Learning can Improve the Effectiveness of Student Learning in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle increased to 90.32%. Thus, the use of Differentiated Learning can be used as an alternative to Improve the Effectiveness of Student Learning in Islamic religious education learning.